The effect of nanocellulose and silica filler on the mechanical properties of natural fiber polymer matrix composites - Endalkachew Gashawtena; Addis Kidane; Belete Sirahbizu (Results in Engineering)
Natural ﬁber-reinforced polymer matrix composites recently got great attention in biomedical applications due to their inherent characteristics such as biocompatibility, lightweight, and biodegradability. However, natural fiber composites suffer from poor mechanical properties and weak interfacial adhesion. It is well documented that the addition of nanofiller has improved the mechanical properties of different synthetic fibers such as glass and carbon composites. The main objective of this paper is to study nanofillers' effect on the mechanical properties of unidirectional false banana fibers reinforced polymer composites. The filler materials, crystalline nanocellulose fibrils, and crystalline nanosilica particles were extracted from sugarcane bagasse and its byproducts. The composite samples were fabricated by adding the nanofillers in unidirectional natural fibers arranged in four fiber orientations (0°, 0o/90o ±45o, and quasi-isotropic), and their tensile, flexural, compression strength, thermal stability, and void content were measured following ASTM standards. The results revealed that adding nanofillers increased the tensile, flexural, and compressive strengths by 16 % (98.83 Mpa), 11 % (161.60 Mpa), and 23 % (114.62 Mpa), respectively. Similarly, at 0° orientation, the addition of nanoparticles enhances the tensile, bending, and compressive modulus by 30 % (15.43 Gpa), 12 % (13.52 Gpa), and 60 % (42.6 Gpa), respectively. On the other hand, the void content was reduced with the addition of nanofillers. The results also revealed that composites with crystalline nanosilica particle fillers had superior thermal stability compared to crystalline nanocellulose fibril fillers. The overall results of this research give the confidence that nano particle-filled natural fiber composites can be used for bio-based engineering applications, such as prosthetic sockets.